A Study on the “Pan Jiao” Thought of Taoism by Modern Protestant Missionaries - LIU, Jingge (Journal of Research for Christianity in China (JRCC), 2026)
This article focuses on how modern Protestant missionaries understand, judge and settle Taoism based on their own belief positions in different stages, that is "pan jiao". From the perspectives of the true knowledge of God, morality, and salvation, it analyzes the interpretations and evaluations of Taoism by missionaries in the three stages, and points out that their “pan jiao” view has undergone a shift from the complete replacement model, the partial replacement model to the fulfillment model. It is believed that this change does not mean that missionaries and Taoism have formed a truly equal religious dialogue, but is closer to a kind of understanding, absorption and integration centered on Christianity.